Characterization of a Conformational Epitope on Hepatitis B Virus Core Antigen and Quasiequivalent Variations in Antibody Binding - Conway, J. F. (American Society for Microbiology, 2003)
We have characterized a conformational epitope on capsids of hepatitis B virus (HBV) by cryo-electron microscopy and three-dimensional image reconstruction of Fab-labeled capsids to ∼10-Å resolution, combined with molecular modeling. The epitope straddles the interface between two adjacent subunits and is discontinuous, consisting of five peptides—two on one subunit and three on its neighbor. Together, the two icosahedral forms of the HBV capsid—T=3 and T=4 particles—present seven quasiequivalent variants of the epitope. Of these, only three bind this Fab. Occupancy ranges from ∼100 to ∼0%, reflecting conformational variations in the epitope and steric blocking effects. In the former, small shifts of the component peptides have large effects on binding affinity. This approach appears to hold general promise for elucidating conformational epitopes of HBV and other viruses, including those of neutralizing and diagnostic significance.